Default Solution on Sharia Housing in The View of Private Law and Islamic Law - Tri Lestari Khoirrani; Risma Nur Arifah (Universitas Nurul Jadid, 2021)
Sharia housing with sharia developer system using cash and in house method without involving the bank is thriving, because in the advert mentioned no fines and confiscations. While every financing there is a possibility of contract breach, such as La Tansa Cluster Malang Housing, there are several users doing breach of contract. This breach of contract can cause problems between developer and user so that solution is needed. The goals of this research are determining factors that led to the breach of contract and the efforts to resolve trade breach of contract in La Tansa Cluster Malang in terms of civil code and Islamic laws. This research uses empirical legal research with a sociological juridical approach, a concept approach, and a legislative approach. Data collected by interviews with developer of La Tansa Cluster Malang and the user, and then analyzed using qualitative descriptive analysis methods. The results showed that breach of contract occurred in La Tansa Cluster Malang due to lack of user candidate analysis, postpone payments, family deaths, business failures, serious illness, and inaccurate financial predictions. According to civil code, the efforts to resolve contract breach of sharia housing trade in La Tansa Cluster Malang are doing deliberation, communication, time extension, PPJB canceling (according to the Article 1338 paragraph (2) of Civil Code), and money returning (according to Article 1267 and Article 1248 of Civil Code). While the efforts to resolve the breach of contract in La Tansa Cluster Malang according to Islamic laws are doing deliberation or reconciliation (shulh), communication, time extension (according to surah al-Baqarah (2): 280), PPJB canceling (based on fasakh iqalah), and money returning (based on dhaman al ‘aqdi).